Effects of endothelin on peptide-dependent cyclic adenosine monophosphate accumulation along the nephron segments of the rat. - Tomita, K (1990)
We investigated the tubular action of endothelin in rat nephron segments. The effects of endothelin on arginine vasopressin (AVP)-, parathyroid hormone-, glucagon-, calcitonin-, and isoproterenol-dependent cAMP accumulation were studied. The following nephron segments were microdissected: glomerulus (Gl), proximal convoluted tubule (PCT), cortical and medullary thick ascending limbs of Henle's loop (cTAL and mTAL, respectively), cortical collecting duct (CCD), outer medullary collecting duct (OMCD), and inner medullary collecting duct (IMCD). Endothelin dose dependently (10(-8)-10(-10)M) inhibited AVP-dependent cAMP accumulation in CCD, OMCD, and IMCD. This effect was independent of the presence or absence of phosphodiesterase inhibitor, 3-isobutyl-1-methylxanthine, Ca channel blocker nicardipine, or indomethacin, but was abolished in the presence of protein kinase C inhibitor H-7. Protein kinase C stimulator dioctanoyl glycerol mimicked the effect of endothelin. On the other hand, endothelin had no inhibitory effect on AVP-dependent cAMP accumulation in cTAL or mTAL, parathyroid hormone-dependent cAMP accumulation in Gl and PCT, or glucagon-, calcitonin-, and isoprotereol-dependent cAMP accumulation in OMCD. We conclude that endothelin specifically inhibits AVP-dependent cAMP accumulation in CCD, OMCD, and IMCD through activating protein kinase C. This effect possibly has a role in maintaining urine volume to counteract the decrease in GFR caused by endothelin itself.